Recent Trends in Studies on Botanical Fungicides in Agriculture - Yoon, Mi-Young; Cha, Byeongjin; Kim, Jin-Cheol (The plant pathology journal, 2013)
Plants are attacked by various phytopathogenic fungi. For many years, synthetic fungicides have been used to control plant diseases. Although synthetic fungicides are highly effective, their repeated use has led to problems such as environmental pollution, development of resistance, and residual toxicity. This has prompted intensive research on the development of biopesticides, including botanical fungicides. To date, relatively few botanical fungicides have been registered and commercialized. However, many scientists have reported isolation and characterization of a variety of antifungal plant derivatives. Here, we present a survey of a wide range of reported plant-derived antifungal metabolites.